2005
DOI: 10.1111/j.1365-3156.2004.01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Blood-brain barrier in falciparum malaria*

Abstract: SummaryPlasmodium falciparum malaria is the most important parasitic disease infecting the central nervous system of humans worldwide. The pathogenesis of the neurological complications of falciparum malaria remains unclear. In particular, how do asexual parasites confined to the vascular space of the brain cause neuronal impairment? The evidence for a breakdown in the blood-brain barrier (BBB) is conflicting. In some animal models of malaria, there is evidence of breakdown of the BBB, but the data from humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…CM appears as a diffuse encephalopathy commonly presenting with headache, agitation, frank psychosis, seizures and impaired consciousness, and occasionally with brainstem signs or focal neurological signs such as hemiplegia and cranial nerve palsies [8,9]. According to the World Health Organization (WHO) clinical criteria, CM is defined as a potentially reversible, diffuse encephalopathy causing a Glasgow coma score of 11/15 or less, often associated with fitting, in the absence of other factors that could cause unconsciousness such as coexistent hypoglycemia or other CNS infections [10].…”
Section: Introductionmentioning
confidence: 99%
“…CM appears as a diffuse encephalopathy commonly presenting with headache, agitation, frank psychosis, seizures and impaired consciousness, and occasionally with brainstem signs or focal neurological signs such as hemiplegia and cranial nerve palsies [8,9]. According to the World Health Organization (WHO) clinical criteria, CM is defined as a potentially reversible, diffuse encephalopathy causing a Glasgow coma score of 11/15 or less, often associated with fitting, in the absence of other factors that could cause unconsciousness such as coexistent hypoglycemia or other CNS infections [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, several studies also reported a crucial role for ICAM-1 in malaria pathogenesis, and notably, ICAM-1-deficient mice are protected from ECM (16). The combined effect of these pathological events is associated with disruption of the physical integrity of the blood-brain barrier (BBB) and the development of brain edema, leading to coma and, ultimately, death (2,(17)(18)(19)(20). One of the characteristic features of ECM is the increased sequestration of CD4 ϩ and CD8 ϩ T cells, which have been reported to be associated with disease pathogenesis (21,22).…”
mentioning
confidence: 99%
“…The sequestration may impair blood flow in the microcirculation and contribute to the CNS effects. The parasites are largely confined to the intravascular compartment, but because the blood-brain barrier is mildly impaired in severe malaria (Gitau and Newton, 2005), compounds produced by the parasite may influence neuronal function. Cytokines, in particular the proinflammatory cytokines such as tumor necrosis factor and interleukin are thought to be involved, probably effecting the CNS through nitric oxide (Clark et al, 1991).…”
Section: Cns Manifestations Of Acute Falciparum Malariamentioning
confidence: 99%